자가 골연골 이식술 이후에도 지속적으로 통증이 지속되는 내측 거골의 골연골 병변 환자에서 시행된 과상부 절골술 및 비골 절골술: 증례 보고 - 최준영; 서진수; Jun Young Choi; Jin Soo Suh (대한족부족관절학회지, 2025)
Osteochondral lesions of the medial talar dome can be challenging to treat, particularly in cases with a large lesion or a subchondral cyst. Autologous osteochondral transplantation harvested from the knee joint after a medial malleolar osteotomy has been considered an effective treatment option in such scenarios. Despite the favorable outcomes of a supramalleolar osteotomy to realign the mechanical axis of the lower limb in cases of medial talar dome osteochondral lesions, the available literature remains limited to a few studies. This case report presents a woman in her early 40s with persistent pain following autologous osteochondral transplantation for a medial talar dome osteochondral lesion. The patient underwent a supramalleolar osteotomy and a fibular osteotomy to achieve valgus realignment of the weight-bearing axis. The clinical and radiological outcomes were evaluated over a follow-up period of more than 1 year, and the relevant literature was reviewed to highlight the potential benefits of this approach.